Influence of the Bolsa Família program on nutritional status and food frequency of schoolchildren - Ariene Silva do Carmo; Lorena Magalhães de Almeida; Daniela Rodrigues de Oliveira; Luana Caroline dos Santos (Elsevier, 2016)
Abstract Objective To evaluate the food frequency and nutritional status among students according to participation in the Bolsa Família program funded by the government. Methods Cross-sectional study carried out with students from the fourth grade of elementary school in the municipal capital of the southeastern region of Brazil. Food consumption and anthropometry were investigated by a questionnaire administered in school, while participation in the Bolsa Família program and other socio-economic information was obtained through a protocol applied to mothers/guardians. Statistical analysis included the Mann-Whitney test, the chi-squared test, and Poisson regression with robust variance, and the 5% significance level was adopted. Results There were 319 children evaluated; 56.4% were male, with a median of 9.4 (8.6-11.9) years, and 37.0% were beneficiaries of Bolsa Família program. Between the two groups, there was high prevalence of regular soda consumption (34.3%), artificial juice (49.5%), and sweets (40.3%), while only 54.3% and 51.7% consumed fruits and vegetables regularly, respectively. Among participants of Bolsa Família program, a prevalence 1.24 times higher in the regular consumption of soft drinks (95% CI: 1.10-1.39) was identified compared to non-beneficiaries. The prevalence of overweight was higher in the sample (32.9%), with no difference according to participation in the program. Conclusion The study found increased consumption of soft drinks among BFP participants. The high rate of overweight and poor eating habits denote the need to develop actions to promote healthy eating, especially for the beneficiaries of the Bolsa Família program, to promote improvements in nutritional status and prevent chronic diseases throughout life.